Evaluasi Kinerja Motor Coal Feeder Di PLTU Tenayan Raya Terhadap Pengaruh Perubahan Frekuensi - Dedi Noviandri; Elvira Zondra; Atmam Atmam (JURNAL TEKNIK, 2022)
Induction motor is an AC type motor that works due to the induced stator current as a result of the relative difference between the rotor rotation with the rotating field produced by the stator current. Induction motor is called asynchronous motor because the rotation of the motor shaft is not the same as the rotation of the stator magnetic field. Coal feeder motor is a three-phase induction motor whose speed regulation is regulated by ‘Variable Speed Drive (VSD)’. The coal feeder motor functions as a conduit for the distribution of coal fuel into the combustion chamber in the boiler which aims to process the combustion in heating water in the pipe wall (walltube) which will be used as steam driving the turbine. Before supplying coal, pay attention first to the amount of coal entering the coal feeder, because it will affect coal flow and motor performance. The more coal that enters the coal feeder, the greater the flow of coal, as well as the high speed of the motor will increase the flow of coal into the furnace. From the research results, a frequency of 4 Hz obtained coal feeder motor speed at 115.2 rpm, with an induction torque of 7.89 Nm, coal flow of 17.16 t/h and efficiency of 32.76% and a frequncy of 10 Hz obtained coal feeder motor speed of 288 rpm with induction torque of 4.48 Nm, coal flow of 42.9 t/h and efficiency of 41.7%.